2004
DOI: 10.1128/jvi.78.23.13197-13206.2004
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Characterization of a Soluble Form of Tomato Spotted Wilt Virus Glycoprotein G N

Abstract: Tomato spotted wilt virus (TSWV), a member of the Tospovirus genus within the Bunyaviridae, is an economically important plant pathogen with a worldwide distribution. TSWV is transmitted to plants via thrips (Thysanoptera: Thripidae), which transmit the virus in a persistent propagative manner. The envelope glycoproteins, G N and G C , are critical for the infection of thrips, but they are not required for the initial infection of plants. Thus, it is assumed that the envelope glycoproteins play important roles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
48
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 65 publications
7
48
0
2
Order By: Relevance
“…Some studies on TSWV membrane structure supports the existence of a Gc protruding structure outside the particle with four, but not five transmembrane domains [16,37]. Other studies, though, suggest five transmembrane domains in TSWV [58,59]. In our analysis, however, five transmembrane domains as found in CSNV and ZLCV (Fig.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Some studies on TSWV membrane structure supports the existence of a Gc protruding structure outside the particle with four, but not five transmembrane domains [16,37]. Other studies, though, suggest five transmembrane domains in TSWV [58,59]. In our analysis, however, five transmembrane domains as found in CSNV and ZLCV (Fig.…”
Section: Discussionsupporting
confidence: 80%
“…The real topology of CSNV and ZLCV or even other tospoviruses, especially TSWV should be urgently unraveled. The role of glycosylations in the Gn and Gc protein is still not well elucidated [58,59], but they are thought to have a positive effect on the virus uptake in animal cells since many identified viral ligants to cellular receptors are viral glycoproteins. In our study, glycosilation sites were predicted and showed to be identical in CSNV and ZLCV, except that in the first glycosilation site of CSNV was Oglicosilated while that of ZLCV was N-glycosilated.…”
Section: Discussionmentioning
confidence: 99%
“…Modeling the structure of a bunyavirus G C protein revealed that the GPs may be class II fusion proteins, and sequence comparisons showed TSWV G N protein shares sequence similarity with another viral attachment protein, sindbis virus E2 (23). These data are supported by findings that TSWV G N likely plays a role in virus attachment to thrips midgut epithelial cells (10), and that G C is cleaved at acidic pH, consistent with it serving as a fusion protein activated at low pH (24). Determining the sequence of mature GPs and solving their crystal structure will be critical to understanding their function and importance of the amino acid at position 459.…”
mentioning
confidence: 68%
“…The experiment consisted of two treatments, virus-exposed and nonexposed L1s, and each experiment was conducted five independent times, i.e., biological replicates. Four replicates were used for differential protein analysis, and one replicate was used for Western blot analysis using the methods of Whitfield et al (80).…”
mentioning
confidence: 99%